The relation of prostatic acid phosphatase and prostate specific antigen with tumour grade in prostatic adenocarcinoma: an immunohistochemical study. - (:unkn) unknown (My University, 1990)
This study examines the relationship between the presence of prostatic acid phosphatase (PAP) and prostate specific antigen (PSA) in tissue, the serum PAP and PSA levels and tumour grade in prostatic adenocarcinoma. Thirty-three tumours were studied by the indirect immunoperoxidase method for PAP and PSA production. Thirty-one of them were stained positive for both markers. The remaining two which previous histopathological studies suggested were transitional cell carcinoma, stained negative. In primary tumours there was a weak trend for poor immunoreactivity in high grade neoplasms but the correlation was not significant. The elevated serum PAP and PSA levels did not correlate with the intensity of staining in the tissue.